Miniature as a way of representation in design studio: a case study. (15th July 2019) - Zeybekoglu, Senem; Sadri, Hossein
Abstract : Purpose: Learning from traditional miniature painting and from recent studies on their modern and creative applications, the purpose of this paper is to identify the key qualifications of miniature and possible ways for using miniature in urban design studios. Following discussions on the pedagogical and professional effects of using miniature in a design studio, the paper introduces De-Urban Design Studio's philosophy and its experience in employing miniature as a way of representation as the case study. Design/methodology/approach: Different from the urban design's professional role which materialized in conventional architectural presentation, miniature appears as a representation way in the search for the appropriate media for the de-urban design's activist model. Findings: Expressing the philosophy of transition design and de-urbanization, and studying some of the miniatures produced in the De-Urban Design studio, this paper sheds light on the possibilities created by the usage of miniature in urban design studio as a communication medium in making the processes of design more inclusiveness, participatory and democratic. Originality/value: The term miniatecture is used for the first time as a representation technique developed in the De-Urban Design Studio co-instructed by the authors of this paper.